Proceedings of the 2019 ACM/SIGDA International Symposium on Field-Programmable Gate Arrays 2019
DOI: 10.1145/3289602.3293911
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soft Errors on Large-Scale FPGA Cloud Computing

Abstract: FPGAs are being used in large numbers within cloud computing to provide high-performance, low-power alternatives to more traditional computing structures. While FPGAs provide a number of important benefits to cloud computing environments, they are susceptible to radiation-induced soft errors, which can lead to silent data corruption or system instability. Although soft errors within a single FPGA occur infrequently, soft errors in large-scale FPGAs systems can occur at a relatively high rate. This paper invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The most commonly occurring sensitive faults of the processor are SEU, Silent Data Corruption (SDC) and Single Event Transient (SET). The SDC is not detectable through the application, randomly occurs through the design and passes incorrect data (Keller and Wirthlin, 2019). SEU corrupts memory values related to devising configuration and active design state in general.…”
Section: Compel 422mentioning
confidence: 99%
“…The most commonly occurring sensitive faults of the processor are SEU, Silent Data Corruption (SDC) and Single Event Transient (SET). The SDC is not detectable through the application, randomly occurs through the design and passes incorrect data (Keller and Wirthlin, 2019). SEU corrupts memory values related to devising configuration and active design state in general.…”
Section: Compel 422mentioning
confidence: 99%
“…The effect on SEUs within large-scale Field Programmable Gate Array (FPGAs) systems was discussed by [ 55 ]; they found that an SEU can be expected every 3.75 h within a 100,000 FPGAs system. Such errors most likely caused the acceleration problem within Toyota vehicles [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, datacenter market leaders increasingly integrate FPGA System-on-Chip (SoC) in their infrastructure to target complex AI applications. Companies like Microsoft, Amazon Web Services, and Baidu scale up AI and high-performance applications on hundreds of thousands of Intel and Xilinx FPGA devices [1].…”
Section: Introductionmentioning
confidence: 99%